Injection Sclerotherapy in Encysted Hydrocele in Paediatric Population - Umar Jamal Khan, Uzma Mumtaz, Muhammad Amjad Chaudhary, Murad Habib (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the role of Sclerotherapy for treating encysted hydrocele in the paediatric population. Study Design: Prospective Study Place and Duration of Study: Department of Paediatric Surgery, Children Hospital Pakistan Institute of Medical Sciences, Islamabad for six months (1st November,2021 to 30th April,2022) Patients and Methods: This study on the captioned topic involved 39 patients aging 2 to 12 years who attended the outpatient department with the complaints of scrotal swelling. In order to rule out non-communicationg hydroceles, these patients were examined clinically and scrotal ultrasound was advised to all the patients which was carried out by them accordingly. In this study, the single team performed the above said procedure on Operation theatre days regularly. The incidence of complications was also monitored with each follow up visits on 1st, 3rd and 6th weeks after the procedure. Results: Study was conducted on 39 children having mean age 4.77 ± 2.860. Pre and post volumes of hydrocele fluid were satistically significant (p≤0.05) with average of 9.00 and 3.269 respectively. Complication rates were decreasing at every follow-up and these were not statisticaly significant (p≥0.05), recurrence complication was significant (p≤0.05). Conclusion: Sclerotherapy has been found to be a positive alternate approach, which is simpler to perform, less time consuming and involving lower complication rate. Keywords: Encysted Hydrocele, Paediatric Population, Sclerotherapy